Dependent Element and Free Actions of Centralizer and Reverse Centralizer on Prime and Semiprime Semirings - Rasheed, Maryam K.; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2019)
This paper develops the work of Mary Florence et.al. on centralizer of semiprime semirings and presents reverse centralizer of semirings with several propositions and lemmas. Also introduces the notion of dependent element and free actions on semirings with some results of free action of centralizer and reverse centralizer on semiprime semirings and some another mappings.